A Solid‐State Aqueous Electrolyte‐Gated Field‐Effect Transistor as a Low‐Voltage Operation Pressure‐Sensitive Platform - Zhang, Qiaoming; Leonardi, Francesca; Pfattner, Raphael; Mas‐Torrent, Marta (Advanced materials interfaces, 2019)
Flexible pressure sensors are increasingly impacting a wide variety of novel applications such as wearable health care sensors, in vivo monitoring, and even artificial skin. As a fundamental device component, organic field‐effect transistors (OFETs) are of great interest due to their inherent advantages related to low‐cost solution fabrication processes and compatibility with plastic substrates. During OFET fabrication, it is almost impossible to avoid the water traces in the organic semiconductor (OSC) active layer, especially when ambient solution processing techniques are employed. Water exhibits a strong influence on the electrical performance in OFETs, such as hysteresis and nonideal transfer characteristics. Here, it is shown that the presence of water in OSCs also results in pressure‐sensitive devices caused by the modification of the water dipole alignment. This exciting phenomenon is exploited in a novel OFET, namely, hydrogel‐based electrolyte‐gated organic field‐effect transistor (HYGOFET), where a soft water‐based hydrogel layer is employed as a dielectric layer. The hydrogel layer plays two major contributions: 1) providing a constant saturated humidity environment and 2) reducing the operation voltage. The HYGOFET exhibits a high electrical performance and relative long‐term stability. Importantly, this device also exhibits an excellent pressure response in the low‐pressure regime (<10 kPa) working with a very low power consumption. A novel pressure‐sensitive platform based on a solid‐state aqueous electrolyte‐gated field‐effect transistor is presented. By assembling a hydrogel dielectric layer, a high electrical performance and long‐term stability hydrogel‐based electrolyte‐gated organic field‐effect transistor device is achieved. In addition, this device is exploited as a low‐consumption pressure sensor driven by the modification of the water dipole alignment within the organic semiconductor layer.